2009
DOI: 10.1258/acb.2009.009059
|View full text |Cite
|
Sign up to set email alerts
|

Macroprolactin on the Advia Centaur: experience with 409 patients over a three-year period

Abstract: Introduction: Macroprolactin (MPRL) is an important source of interference that may lead to misdiagnosis and mismanagement of hyperprolactinaemic patients. Prolactin assays exhibit considerable variation in the detection of MPRL. In this study, we examine the requirement for polyethylene glycol (PEG) precipitation in the analysis of hyperprolactinaemia detected by the Advia Centaur as it has a relatively low reactivity with MPRL. Methods: Four hundreds and sixty-four hyperprolactinaemic samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 11 publications
4
16
0
Order By: Relevance
“…Patients with pronounced elevation in prolactin, those with TSH outside the laboratory’s reference interval and pregnant women were excluded from the study to avoid inclusion of obvious biases in prolactin data. Patients with macroprolactin and other causes of mildly increased prolactin were not excluded, but these are likely to have a minimal effect given the large number of patients and the low incidence of macroprolactin (<5% of hyperprolactinaemia using the Siemens method) 6,7 . The presence of macroprolactin is likely to have affected all groups equally and thus would not affect the differences found between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pronounced elevation in prolactin, those with TSH outside the laboratory’s reference interval and pregnant women were excluded from the study to avoid inclusion of obvious biases in prolactin data. Patients with macroprolactin and other causes of mildly increased prolactin were not excluded, but these are likely to have a minimal effect given the large number of patients and the low incidence of macroprolactin (<5% of hyperprolactinaemia using the Siemens method) 6,7 . The presence of macroprolactin is likely to have affected all groups equally and thus would not affect the differences found between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…4% for one such immunoassay, although 9 of the 16 patients whose serum samples contained macroprolactin also had raised monomeric prolactin). 37 Screening for macroprolactin in all serum specimens with total prolactin concentrations above an agreed cut-off is therefore widely recommended.…”
Section: Subjects With Macroprolactinaemia and Other Macrocomplexesmentioning
confidence: 99%
“…This is illustrated in a recent report that indicated that 25% of prolactin requests came from psychiatry. 4 …”
Section: Workloadmentioning
confidence: 99%